Analytical prediction of seismic behavior of RC joints and columns under varying axial load. (1st November 2018) - Shayanfar, Javad; Bengar, Habib Akbarzadeh; Parvin, Azadeh
Highlights: A new methodology was developed to consider the influential effect of axial load variations. A new analytical joint model considering nonlinearities in the joint region was developed. Considering the effects of axial load variations noticeably improved the predictions. The proposed analytical procedure can easily be followed without the need of any structural analysis software program. Abstract: In this study, an analytical model for predicting nonlinear behavior of exterior reinforced concrete (RC) beam-column joints under varying axial load was developed. The main focus was given on the assessment of the effect of axial load variations on the response of RC joints and columns. During seismic actions, overturning moments are produced by lateral loads that are translated as axial loads in the columns. It leads to compressive axial force on one side of the structure along with tensile on the opposite. It can overwhelm nonlinear behavior associated with axial, flexural, shear stresses of RC columns and joints. To simulate and evaluate these nonlinearities, a beam- column joint model consisted of rotational springs were developed. The characteristics of joint spring could be computed using principle tensile stress-joint rotation relation ( pt versus θj ) in the joint core depending on the type of the beam bar anchorage. Therefore, for the joints with various beam bar anchorage details, pt versus θj relations in the joint core were proposed. A new theoretical methodology was also developed to consider the effect of the axial load variations in determining characteristics of rotational springs. To assess the accuracy and reliability of the analytical model, it was compared through experimental data available in the literature. The results showed that the proposed analytical model could predict the experimental response of poorly detailed RC beam-column joints under varying or constant axial loads with reasonable precision. Furthermore, parametric studies were carried out to highlight the overwhelming effect of axial load variations on RC beam-column joints and columns. The simple analytic procedure would make the model sufficiently suitable for practical applications.